Control authority, business strategy, and the characteristics of management accounting information systems - Ramli, Ishak; Iskandar, Denny (Elsevier Ltd., 2014)
Phenomenon of value to the information in Indonesia is that information is not used for making decision but for official concern.Using 195 response respondents from 430 managers of the manufacturing companies mostly from Jakarta, Indonesia, we analyse and test whether the formal, and informal structures control authority and business strategy influence the characteristics of management accounting information system (MAIS). We found that the formal, informal authority and business strategy significantly and positively influence the characteristics of MAIS.The informal and business strategy have big effect on the MAIS for decision making, while the formal one has very much less effect.The business strategy has a very dominant influence on developing the MAIS.The Formal authority is opposite and not in line with the informal one.Business strategy is more adaptive to the informal authority than the formal one.This provided that managers’ business strategy moderately be based not by the formal information provided, but the informal one.